2019
DOI: 10.5004/dwt.2019.24302
|View full text |Cite
|
Sign up to set email alerts
|

Electrocoagulation treatment of industrial wastewater including textile dyeing effluent – a review

Abstract: Electrocoagulation (EC) treatment can be used as an effective alternative to the existing treatment methods. It is a distinct, economical and an environmental friendly choice for meeting water treatment discharge standards and compliance requirements. Due to improved material of construction and process design, the EC process is widely accepted. Presently, this process has gained attention due to its ability to treat large volume of effluent with low cost. The EC process includes the in-situ generation of coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Studies have shown that temperature increases microbial activity and chemical reaction in the treatment plant (Altaher & Alghamdi, 2011 ; Mhlanga & Brouckaert, 2013 ; Tony, 2019 ). Moreover, the decomposition and removal efficiency of biodegradable organic pollutants and compounds, are highly dependent on temperature in the treatment plant (Sen et al, 2019 ; Uddin, 2021 ). Conversely, the increase of temperature beyond the limits could deplete the dissolved oxygen and increase the operational cost of the treatment plant (Bhave et al, 2020 ; Nawaz & Ahsan, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that temperature increases microbial activity and chemical reaction in the treatment plant (Altaher & Alghamdi, 2011 ; Mhlanga & Brouckaert, 2013 ; Tony, 2019 ). Moreover, the decomposition and removal efficiency of biodegradable organic pollutants and compounds, are highly dependent on temperature in the treatment plant (Sen et al, 2019 ; Uddin, 2021 ). Conversely, the increase of temperature beyond the limits could deplete the dissolved oxygen and increase the operational cost of the treatment plant (Bhave et al, 2020 ; Nawaz & Ahsan, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on Mhlanga and Brouckaert ( 2013 ) study, the levels of DO vary with wastewater temperature, characteristics of wastewater and mixing system, season, time of day, and rate of flow. Furthermore, releasing a low level of DO into the surface water highly affects the aquatic animals and forms intermediate pollutants due to the presence of organics in the wastewater (Asses & Ayed, 2021 ; Sen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the decomposition and removal efficiency of biodegradable organic pollutants and compounds, are highly dependent on temperature in the treatment plant (Sen et al, 2019;Uddin, 2021). Conversely, the increase of temperature beyond the limits could deplete the dissolved oxygen and increase the operational cost of the treatment plant (Nawaz and Ahsan, 2014;Bhave et al, 2020).…”
Section: Fig 3 Operational Control Influent and Effluent Textile Wast...mentioning
confidence: 99%
“…Examples include physical or chemical flocculation, membrane filtration, electro kinetic coagulation, electrochemical destruction, and precipitation [11]. These types of technologies are inefficient, expensive, and have low adaptability to diverse types of dye effluent.…”
Section: Introductionmentioning
confidence: 99%